If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = 3y + -16 Reorder the terms: 26 = -16 + 3y Solving 26 = -16 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 26 + -3y = -16 + 3y + -3y Combine like terms: 3y + -3y = 0 26 + -3y = -16 + 0 26 + -3y = -16 Add '-26' to each side of the equation. 26 + -26 + -3y = -16 + -26 Combine like terms: 26 + -26 = 0 0 + -3y = -16 + -26 -3y = -16 + -26 Combine like terms: -16 + -26 = -42 -3y = -42 Divide each side by '-3'. y = 14 Simplifying y = 14
| 9x+24=2x+3 | | 4cos^2x+3cosx=0 | | 158=67-x | | 16y=0.6y | | -4=y-7 | | -5a-(3a-7)= | | x^2-2x+8=20 | | b(y-b)=d(y-d) | | -5a-3a-7= | | -2+3(-6y-7)=-5(-5y-1)+2 | | 6=3+y | | x^2+3x-7=32 | | x^2+x+10=35 | | x^2+3x+4=16 | | x+10=24-x | | x^2+x-7=3 | | x^2+x-7=14 | | 0=44x^2-88x+74 | | 0=44x^2-88t+74 | | x^3+3=14 | | 24=4m | | -7(2x+3)+11x= | | x^2+2x+1=40 | | G=9/2(p-67) | | x=1-13/5 | | 5x+13y+5=0 | | -11-(-15)= | | -3(4r-80)=-36 | | 180=4/(x-4) | | y=2(x-7) | | w-(4/2/5)=(9/3/5) | | 11-x=19 |